Rivers by design state power and the origins of U.S. flood control - O'Neill, Karen M. 1959- (Duke University Press, 2006)
Infrastructure builds the state -- The founding principles of river development -- The Mississippi River : becoming the nation's river -- The Mississippi River : resentment leading to Civil War -- The Mississippi River : postwar reunification, postwar aid -- The Sacramento River : miners versus farmers -- The Sacramento River : capitalists unify for development -- Federal aid for the Mississippi and Sacramento Rivers -- The fully designed river -- A nationwide program for flood control -- Rivers by design -- Mississippi Valley river improvement conventions -- Mississippi River Levee Association, Executive Committee